Effects of sleep deprivation on sleep and sleep electroencephalogram in secretin-receptor knockout mice - Moridera Aiko; Fujihara Hiroaki; Cherasse Yoan; Mugishima Go; Fujiki Nobuhiro (Neuroscience Research)
Recent studies has consistently demonstrated a relationship between secretin and autism-like behavior in mice. Therefore, secretin-receptor knockout (SCTR-KO) mice are used to study autism. However, with respect to humans, some studies have reported that secretin administration could improve autistic symptoms in contrast to other studies. A consistent finding revealed that several patients with autism spectrum disorders (ASD) experience comorbid sleep disorders. To examine the relationship between secretin and sleep, we recorded the core body temperature and locomotor activity of SCTR-KO (-/-) and wild-type (WT) (+/+) mice in the baseline condition and after 4 h of sleep deprivation. No significant differences were observed between the SCTR-KO and control mice in the baseline condition. However, during the first dark period following sleep deprivation, we observed an increase in non-rapid eye movement sleep in the SCTR-KO group, which demonstrated that the absence of secretin induces fragmentation making it difficult for the SCTR-KO mice to maintain sleep and wakefulness. Our results follow previous reports that a large proportion of patients with ASD complain of drowsiness and decreased focus during the day. Secretin functions as an intestinal peptide that neutralizes gastric acid and as a neuropeptide in the brain; it also affects social cognitive behavior and acts as a neurotrophic factor. We have proposed that secretin might be a contributing factor to the modulation of sleep.